Analysis of Xi Jinping’s foreign policy towards Southeast Asia: strategies, interests, and dimensions - Rubiolo, Florencia (2020)
This work analyzes Xi Jinping’s foreign policy towards Southeast Asia, focusing on the political-strategic and economic dimensions. The initial assumption is that its actions and strategies show greater visibility and dynamism than those carried out by its predecessors, both regionally and globally.  From the literature review, it is identified that China combines, on the one hand, an assertive foreign policy in matters of territorial sovereignty such as the defense of its maritime sovereignty in the South China Sea and; on the other, economic and trade integration based on interdependence and multilateralism, through the strengthening of regional ties within the framework of ASEAN + 3, the China-ASEAN Free Trade Area and the Belt and Road Initiative.  This article focuses on the complementarity of the actions and initiatives of Chinese foreign policy towards the region, starting from the development of a holistic strategy of global projection, based on the consolidation of a regional space of power and the consequent construction of leadership.